RESTORATIVE JUSTICE AS AN EFFORT TO RESTORE VICTIMS' RIGHTS - Sipayung, Parlin Dony; Candra, Satria; Tungkir, Therecsya BR; Br Sinaga, Clarita Septiana; Napitu, Seimei; Situmorang, Rio Irawan Maruba (Inspiring Law Journal, 2025)
The mechanism for resolving cases based on restorative justice is based on deliberation and consensus where the parties are asked to compromise to reach an agreement. Each individual is asked to give in and put the interests of society above personal interests in order to maintain harmony together. The concept of deliberation has proven to be more effective in resolving disputes in society amidst the failure of the role of the state and the courts in providing a sense of justice. The main objective of restorative justice is to empower victims where perpetrators are encouraged to pay attention to the victim's recovery to their original state, whether the victim's material, emotional and social needs are met. This is done because the success of restorative justice is measured by the extent of the losses that have been restored by the perpetrator to the victim, not by the severity of the sentence imposed by the judge on the perpetrator. Restorative justice from a victimology perspective can be applied in resolving criminal cases in Indonesia in order to reduce or restore the suffering of crime victims, which can be realized by providing compensation and restitution